A prospective study to evaluate the role of hysterolaparoscopy in infertility - Kale, Pooja Subhash; Noronha, Sylvia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Infertility is one of the most important and underappreciated reproductive health problems in developing countries. The aim of the present study was to evaluate the role of hysterolaparoscopy in infertility. Methods: It was observational prospective study. In this study, 50 patients in the age group of 20-40 years who are anxious to conceive formed the study group. All women were subjected to a detailed history taking followed by clinical examination. Results: Out of 50 cases studied, 30 (60%) were of primary infertility while, 20 (40%) were of secondary infertility. Laparoscopic findings were as follows, 28% had polycystic ovaries, 20% had endometriosis, 18% had tubal factors, 18% had adhesions, and 8% had fibroids while 4% had PID. Hysteroscopic findings were uterine septum in 16%, T shaped cavity in 14%, shaggy-hyperplastic endometrium in 10% while adhesions and polyps in 8% and 4% respectively. 16 women (32%) conceived after the procedure during the study period. Conclusions: It is concluded that while investigating the causes of female infertility combined simultaneous diagnostic laparoscopy and hysteroscopy with operative interventions wherever indicated should be performed in all infertile patients before treatment, especially in women with age more than 30 years.